PENERAPAN KONSEP COMMUNITY BASED TOURISM DALAM PENGEMBANGAN PARIWISATA DI DESA WISATA NGLURAH - Yeslinda Rupidara; Widyaningtyas (Mount Hope Economic Global Journal, 2024)
Nglurah Tourism Village is one of the tourist villages located on the slopes of Mount Lawu, Tawangmangu District, Karanganyar Regency. This tourist village is known as a tourist village that has various tourism potentials, both natural potential, cultural potential, and also man-made potential. This research aims to analyze how the concept of Community Based Tourism (CBT) is applied in Nglurah Tourism Village, as well as its impact on the local community with five (5) principles put forward by UNEP and WTO, namely economic principles, social principles, cultural principles, political principles, and environmental principles as indicators. The method used in this research is descriptive with a qualitative approach, using data collection techniques through interviews, observation, and documentation. The results of this study show that the application of the CBT concept in Nglurah Tourism Village has brought positive impacts to the local community, such as local economic development, preservation of local traditions and culture, and increased community participation in tourism management. In addition, the CBT concept also strengthens the relationship between local communities, and improves the quality of life of the community. The conclusion of this study is that the application of the CBT concept in Nglurah Tourism Village is quite active and has a significant positive impact on various aspects of community life and the local community can be said to be ready for tourism activities.